Heterogenitas Ulumul Qur’an dalam Manuskrip Mushaf Al-Qur’an - Muhamad Khabib Imdad (Lajnah Pentashihan Mushaf Al-Qur'an, 2025)
This study discusses the heterogeneity of the ulumul qur'an in the ancient mushaf stored in the Great Mosque of the Surakarta Palace, namely in the use of rasm and qira'at aspects. The mushaf is a collection of Sinuhun Pakubuwana X written by Sayyid Ibrahim bin 'Abdullah al-Jufri in the mid-19th century AD. This research is qualitative research using the library research method. The data collection methods applied were observation, documentation, interviews and digitalization, while data analysis used was the descriptive-analytical method. Through this article it can be seen that the mushaf uses two rasm, namely rasm usmani and imla‘i, while in Indonesia it is more common to use only rasm usmani. This phenomenon has similarities with several other findings made by a number of researchers, but this is found in several mushafs such as in Klaten, Bali, Bonjol and Payakumbuh, and Subang. Meanwhile, from the aspect of qira'at, the mushaf mixes the reading model of Imam Nafi' with rawi Qalun, Imam Abu 'Amr rawi ad-Durri, and Imam 'Asim rawi Ḥafs, whereas in the tradition of reading the Qur'an in Indonesia it is more common to use the model third reading.